Digital Consumer Insights and Strategy Formulation for Local Fashion Business Development - Hafidza Octa Auladzy; Rina Djunita Pasaribu (Penerbit Goodwood, 2026)
Purpose: This study examines Human Greatness Labs (HGL), a Bandung-based local fashion Small and Medium Enterprises (SME) facing fluctuating sales performance, product quality concerns, and increasingly digital consumer feedback. Grounded in strategic management and dynamic capabilities perspectives, this study identifies internal and external strategic factors, formulates business development alternatives, and determines the priority strategy for strengthening HGL’s competitiveness. Research Methodology: A qualitative exploratory-descriptive single case study was conducted using interviews with nine informants, consisting of five internal and four external informants, supported by company documentation, internal sales data, and e-commerce consumer reviews. The analysis applied the Internal Factor Evaluation (IFE), External Factor Evaluation (EFE), Strengths, Weaknesses, Opportunities, and Threats (SWOT) analysis, Internal External (IE) Matrix, and Quantitative Strategic Planning Matrix (QSPM). Results: The findings show that HGL obtained an IFE score of 2.5677 and an EFE score of 2.8114, positioning the company in Cell V of the IE Matrix, which indicates a hold and maintain strategy. The QSPM analysis identified AS3 as the priority strategy, with the highest Total Attractiveness Score (TAS) of 6.2427. Conclusions: HGL should prioritize comfortable, functional, and trend-relevant basic wear development through color innovation, improved cutting, and digital consumer insights before pursuing broader market expansion. Limitations: The single case study design limits statistical generalization to other local fashion brands. Contributions: This study contributes to strategic management research by integrating stakeholder interviews, sales data, and online consumer reviews into evidence-based strategy formulation for Indonesian local fashion SMEs.